Nontraumatic Emergency Laparotomy: Surgical Principles Similar to Trauma Need to Be Adopted?. Issue 11 (November 2017) - Singh-Ranger, Deepak; Leung, Edmund; Lau-Robinson, Mei-Ling; Ramcharan, Sean; Francombe, James
Abstract: Objectives: In 2011, the Royal College of Surgeons published Emergency Surgery: Standards for Unscheduled Care in response to variable clinical outcomes for emergency surgery. The purpose of this study was to examine whether different treatment modalities would alter survival. Methods: All patients who underwent emergency laparotomy between April 2011 and December 2012 at Warwick Hospital (Warwick, UK) were included retrospectively. Information relating to their demographics; preoperative score; primary pathology; timing of surgery; intraoperative details; and postoperative outcome, including 30-day mortality, were collated for statistical analysis. Results: In total, 91 patients underwent 97 operations. The median age was 64 years (range 50–90, male:female 1:2). Sixty-five percent of cases were obstruction and perforation, and 66% of all operations were performed during office hours. The unadjusted 30-day mortality was 15.4%. Compared with nonsurvivors, survivors had a significantly higher Portsmouth-Physiological and Operative Severity Score for the enUmeration of Mortality and Morbidity score ( P < 0.001), prolonged duration of hypotension and use of inotropes ( P = 0.013), higher volume of colloid use ( P = 0.04), and lower core body temperature ( P < 0.05). Grades of surgeons did not influence mortality. Conclusions: The 30-day mortality rate is comparable to the national standard. Further studies are warranted to determine whether trauma management modalities may be adopted to target high-risk patients who exhibit the lethal triad of hypotension, coagulopathy, and hypothermia. Abstract : Emergency laparotomy carries with it high morbidity and mortality. This article examines factors that affect outcome and whether a better-driven protocol can be developed to improve patient outcome.